1999
DOI: 10.1021/la980968x
|View full text |Cite
|
Sign up to set email alerts
|

Study of Structure Formation in Aqueous Solutions of Poly(ethylene oxide)−Poly(propylene oxide)−Poly(ethylene oxide) Block Copolymers by Measuring Rate Constants of the Thermal Cis−Trans Isomerization of an Azobenzene Dye and Self-Diffusion of Copolymer Molecules

Abstract: In aqueous solutions of poly(ethylene oxide) (PEO)−poly(propylene oxide) (PPO)−PEO triblock copolymers (Pluronics P85, F88, and L64), structure formation (micellization) on increasing temperature was followed by determination of rate constants k iso of the thermal cis−trans isomerization of 4,4‘-nitroanilinoazobenzene by means of flash photolysis in H2O and D2O. The kinetic solvent isotope effect k iso,H 2 O/k iso,D 2 O indicates that the azobenzene dye molecules are solubilized in a water-rich environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 43 publications
2
41
0
Order By: Relevance
“…We discussed the temperature of the maximum of D determined by means of PFG NMR measurements as cmT of "probe-free" samples [15,16]. Moreover, we have found that ln(bulk viscosity) vs. 1/T plots of 10% F88 solutions, and density vs. 1/T plots of solutions of ≥5% P85 and 10% F88, respectively, show also inflection points that can be assigned to micelle formation (see Figs.…”
Section: Cmt-datamentioning
confidence: 92%
See 4 more Smart Citations
“…We discussed the temperature of the maximum of D determined by means of PFG NMR measurements as cmT of "probe-free" samples [15,16]. Moreover, we have found that ln(bulk viscosity) vs. 1/T plots of 10% F88 solutions, and density vs. 1/T plots of solutions of ≥5% P85 and 10% F88, respectively, show also inflection points that can be assigned to micelle formation (see Figs.…”
Section: Cmt-datamentioning
confidence: 92%
“…We determined the cmT values of solutions without probe molecules from intersection points of linear parts of Arrhenius plots of self-diffusion coefficients (PFG NMR) [15,16], and bulk viscosity. Density data were also plotted against 1/T for better comparison and analyzed accordingly.…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 3 more Smart Citations